Cognitive regulation, not behavior regulation, predicts learning. (April 2019) - Modrek, Anahid S.; Kuhn, Deanna; Conway, Anne; Arvidsson, Toi Sin
Abstract: Although inquiry learning has increasingly been a topic of empirical research, there has been little investigation of individual differences in this regard. What makes some students more effective inquiry learners than others? We examined two kinds of self-regulation – cognitive regulation and behavior regulation – as possible predictors of individual differences in middle-school students' inquiry learning performance. Across two studies, one involving middle-class students (n = 135) and one involving students from a lower socioeconomic status underachieving population (n = 21), results were consistent. Cognitive regulation, but not behavior regulation, was associated with more successful inquiry learning. We discuss implications for the role of regulatory processes in inquiry learning and, more broadly, for education.